Epigenetic Analysis of the Human Alpha- and Beta-Globin Gene Clusters - Fathallah, Hassana (2007)
K562 erythroleukemia cells have been widely used as a model for the study of globin gene regulation. A number of agents have been shown to activate or suppress globin gene expression in these cells. However, the molecular effects of these agents on the epigenetic configuration of the α- and γ-globin genes that encode HbF are not known. In this report, we investigated the relationship between globin expression and histone acetylation of the human α- and β-globin clusters in the fetal erythroid environment of K562 cells. Our studies suggest that acetylation of histone H3 may be important in regulating developmental stage-specific expression of the different β-like globin genes while acetylation of both histones H3 and H4 may be important for the regulation of tissue-specific expression of these genes. In contrast, acetylation of both histones H3 and H4 at the α-like globin promoters appears to be important for both developmental stage- and tissue specific-expression. Interestingly, butyrate-induced activation of α-globin gene expression in K562 cells is associated with significant increase in histone acetylation levels while TPA-induced inhibition is associated with decreased histone acetylation at its promoters. In contrast, changes in histone acetylation and DNA methylation do not appear to be important in the regulation of γ-globin gene expression by the same agents. These data suggest that the butyrate-mediated induction of the fetal γ-globin genes in K562 cells is not a direct result of its histone deacetylase inhibitor activity of butyrate on the chromatin of the γ-globin promoters, while the induction of the α-globin genes could be a result of a direct effect of butyrate on chromatin at its promoters. This is another example of the important differences in the molecular mechanisms of regulation of the genes of the α- and β-like globin clusters.